Local Regulation of Thrombin Activity by Factor Xa in Peripheral Nerve Schwann Cells. (10th February 2018) - Gera, Orna; Bushi, Doron; Ben Shimon, Marina; Artan-Furman, Avital; Harnof, Sagi; Maggio, Nicola; Dori, Amir; Chapman, Joab; Shavit-Stein, Efrat
Highlights: The peripheral nervous system contains factor X (FX) and activated factor (FXa) which determines thrombin generation. FX and FXa expression changes significantly in reaction to sciatic injury. Injecting FXa inhibitor apixaban immediately upon nerve injury, decreases thrombin activation and improves motor function. Abstract: Thrombin through its receptor plays an important role in the peripheral nervous system (PNS) but the pathways leading to its generation there are not known. In the blood, activated factor X (FXa) which is formed from factor X (FX) by tissue factor (TF) and factor VII (FVII), cleaves prothrombin into thrombin. We here studied these factors in vivo in mouse sciatic nerve and in vitro in a Schwannoma cell line and provide mRNA, immunoblot and immunohistochemistry evidence that FX and FXa are expressed in the normal and injured peripheral nerve and in Schwannoma cells. Furthermore, TF and FVII were localized histologically to the node of Ranvier in the sciatic nerve. Adding exogenous FXa increased the thrombin levels in sciatic nerve (11.6 ± 1.6 mU/ml compared to 35.2 ± 6 mU/ml p  = 0.02) and in Schwannoma cell line (4.5 ± 0.2 mU/ml compared to 18.1 ± 0.5 mU/ml p  < 0.001), indicating a large reserve of prothrombin. In the injured nerve, FX mRNA was upregulated 1 day after injury compared to normal nerve (103 ± 38 versus 1 ± 0.3 FOI p  < 0.001). FXa protein levels increased 1 h after the injury and then decreased significantly at 1 and 2 days following injury despite an increase in its precursor, FX. Injecting the selective FXa inhibitor apixaban immediately upon injury decreased thrombin activation and improved motor function after nerve injury. The results localize the extrinsic coagulation pathway and FXa to the PNS, suggesting a critical role for FXa in PNS thrombin formation and the possible therapeutic use of selective FXa inhibitors in nerve injuries.